Entrepreneurship development and project management:text and cases - Sarwate, Dilip M (Everest Pub. House, 2009)
Entrepreneurship development and project management:text and cases / Sarwate, Dilip M. -- Pune: Everest Pub. House, 2009 658.421 Sa249e6 6th ed. No. of Copies : 1